(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
By problematizing the relationship between writing and speaking in theatre making, the article, from a practical-theoretical perspective, reconstructs the process of creating the show Por visões by Cia. Passo a 2 de Teatro. It is based on the author’s experience, as a playwright and director invited to the project, that establishes a reflection on listening as a prism for writing, as a form of self-displacement. The stages and procedures used in the preparation of the text are described and analyzed, seeking a broader understanding of the gesture of writing, in its intimate connection with orality, and of what today can be called a theatrical text.